The neurologist's role in disabling multiple sclerosis: A qualitative study of patient and care provider perspectives. (June 2020) - Falet, Jean-Pierre R; Deshmukh, Shriya; Al-Jassim, Abrar; Sigler, Gregory; Babinski, Melanie; Moore, Fraser
Background: Patients with advanced, disabling multiple sclerosis (MS) have few effective treatment options. Little is known about the role that patients and their care providers want their neurologist to fill in this situation. Objective: To better understand the role that patients with disabling MS and their care providers want their neurologist to have in their care. Methods: In this exploratory qualitative study, we conducted semi-structured interviews with 29 participants (19 patients with severe disability due to MS and 10 care providers). Interview transcripts were analyzed using inductive thematic analysis. Results: Participants identified three main roles for their neurologist: a source of hope for therapeutic advances, an educator about the disease and its management, and a source of support. Conclusion: Despite sustaining a level of disability that may be refractory to standard medical therapy, patients with disabling MS and care providers continue to value certain roles of their neurologist. The neurologist's role as a source of hope and support in particular has not received enough attention in the literature.